1920
DOI: 10.1002/cber.19200531009
|View full text |Cite
|
Sign up to set email alerts
|

Versuche zur Synthese eines Kohlenwasserstoffs C 14 H 10

Abstract: 2034sierenden Reaktionsgemisch 10 ccm entoommen, wobei die von K n u d s e n I) heschricbene, mit WasserstoEl gefiillte Pipette zur Anwendung kam. Das Aufsaugen fand durch die Wasserstrahl-Pumpc statt, beim .\blassen stromte Wasscrstoff nach, so da13 die Flkssigkeit nicht, rnit Luft in Berkhrnng kam. Zum Eingeben der abpipettierten Meoge in den Destillierkolben wurde der Scheidetrichter abgenommeri. Nach rasch erfolgtem VerschluB wurde nochmals kurze &it Kohlendioxyd hindurchgeleitet, und jetzt erfolgte das Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1934
1934
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…As was the case for the spectrum, the reduced rotational symmetry of the cubic volume leads to infinitely many partial waves featuring in the relation between finite-volume matrix elements and infinite-volume transition amplitudes. This was first pointed out by Meyer in the context of bound state photodisintegration [59], and later revisited for generic 2 → 1 transitions in Refs. [28,29], where it was shown that one can write a relation between a generic finite-volume matrix element, 1; L|J µ (0)|2; L , and the corresponding infinite-volume transition amplitude, H µ 2,1 = 1|J µ (0)|2 .…”
Section: B Transition Amplitudementioning
confidence: 84%
See 1 more Smart Citation
“…As was the case for the spectrum, the reduced rotational symmetry of the cubic volume leads to infinitely many partial waves featuring in the relation between finite-volume matrix elements and infinite-volume transition amplitudes. This was first pointed out by Meyer in the context of bound state photodisintegration [59], and later revisited for generic 2 → 1 transitions in Refs. [28,29], where it was shown that one can write a relation between a generic finite-volume matrix element, 1; L|J µ (0)|2; L , and the corresponding infinite-volume transition amplitude, H µ 2,1 = 1|J µ (0)|2 .…”
Section: B Transition Amplitudementioning
confidence: 84%
“…As demonstrated in Refs. [28,29,59], due to the reduction of rotational symmetry in a cubic volume, transition amplitudes involving different partial waves appear together in finite-volume irreps, leading to R in Eq. ( 17) being a matrix in -space.…”
Section: Discussionmentioning
confidence: 99%
“…The additional factorization breaks translational invariance and the symmetry between directions 1 and 2 and thus leads to a loss of statistics; on the other hand the short-distance fluctuations of the one-line operators can be averaged out separately. Test studies [36] in the d = 3 SU(2) theory show that the three-level algorithm improves on the original Lüscher-Weisz algorithm for r ≥ 0.9fm, a = 0.08fm, the latter being superior at shorter distances. This test concerns the static force in the fundamental representation, but in the higher representations, and also at smaller lattice spacing, we expect the additional factorization to pay off already at shorter distances.…”
Section: Algorithm Implementation and Efficiencymentioning
confidence: 96%
“…spectra and scattering observables, namely that finite-volume matrix elements can be used to extract infinite-volume matrix elements with two-particle asymptotic states [5,12,13,15,16,[36][37][38][39][40][41][42]. The latter are referred to throughout this work as transition amplitudes.…”
Section: Introductionmentioning
confidence: 99%